Genetic variation of Austropuccinia psidii in some species of Myrtaceae as host plants in Java, Indonesia based on simple sequence repeats (SSR) markers - FARAH AULYA FARADILLA; ISTIANA PRIHATINI; SURANTO SURANTO; ARI SUSILOWATI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Faradilla FA, Prihatini I, Suranto, Susilowati A. 2022. Genetic variation of Austropuccinia psidii in some species of Myrtaceae as host plants in Java, Indonesia based on simple sequence repeats (SSR) markers. Biodiversitas 23: 256-263. Austropuccinia psidii is pathogenic rust with a wide host and is considered a biosecurity threat to the Myrtaceae family in many countries. The genetic variation of this rust in Java, Indonesia is poorly reported. Therefore, this study aimed to determine the genetic variation among A. psidii from different Myrtaceae hosts, namely Syzygium polyanthum, S. myrtifolium, and Melaleuca cajuputi from three different locations in Java using seven simple sequence repeats (SSR) markers. Data were collected from 28 A. psidiisamples from three different hosts and locations in Java. The genetic variations of A. psidii were found in six isolates in locus USYD_Pp168, PpSSR161, and PpSSR195*. The results showed that the expected heterozygosity value among 12 isolates of A. psidii is 0.312. The dendrogram illustrates two clusters constructed with cluster I consisting of subcluster IA (S1, S3, S4, S5, K1, K2, K3, K4, and P1) and IB (P2); and cluster II consists of isolates S2 and S6. Principal Coordinate Analysis (PCoA) was used to demonstrate the similarity and dissimilarity among isolates based on microsatellite sites. Axis 1 and 2 explained 87.7 % of the total variations and sep a rated isolate S1, S2, S3, S4, S6 from other isolates, and grouping the rest of isolates together. The dendrogram and PCo analysis demonstrated A. psidii isolates tend to have close genetic similarity based on their host.